Pasang Surut Otonomi Daerah dalam Kerangka NKRI - Fadilah, Sariul; R. Zainul Mushthofa (Universitas Sunan Drajat Lamongan, Indonesia, 2023)
Indonesia is a unitary state formed by a republic. As a unitary state, Indonesia adheres to the principle of decentralization in governance. By giving the opportunity and flexibility to the regions to carry out regional autonomy as wide as possible. The authority of broad autonomy is the discretion of the region to organize government which includes the authority of most areas of government. Especially in a modern state, especially when it is associated with the notion of a welfare state, the number of government affairs cannot be identified, because the autonomy authority covers all aspects of people's lives, especially those related to service affairs and public interests. In addition to being very broad, government affairs can always expand in line with the expansion of the duties of the state and/or government. Likewise, Indonesia in carrying out regional autonomy has more or less adopted the concept of federalism so that it is feared that it will disrupt the stability of Indonesia as a unitary state, because after all the regions, within the unitary state of the Republic of Indonesia are an eenheidstaat, Indonesia will not have regions within its environment that are staat either. Thus the implementation of regional autonomy in a unitary state has its limits.